Optimization of Public Electric Vehicle Charging Stations Locations Using Mixed Integer Linear Programming in The City of Bogor - Firdaus, Fitri Nurul Firdaus; Gunarta, I Ketut Gunarta (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2026)
Although the Indonesian government has issued regulations to encourage the adoption of electric vehicles (EVs), their implementation still faces challenges, particularly the uneven distribution of Public Electric Vehicle Charging Stations (PEVCS). In the City of Bogor, seven PLN-owned PEVCS are concentrated in Central and North Bogor, alongside several privately operated stations and brand-specific charging points. This imbalance highlights the need for an optimized PEVCS location strategy to adequately meet EV charging demand. This study aims to determine the optimal number and type of charging connectors at each proposed PEVCS location in the City of Bogor using a Mixed Integer Linear Programming (MILP) approach. The model recommends installing new PEVCS in areas without charging facilities, totaling nine ultrafast charging connectors: three in West Bogor and two in each of South Bogor, East Bogor, and Tanah Sareal. The total investment cost for the proposed PEVCS network is IDR 9,751,500,000, while the total daily user travel cost is IDR 243,189. Sensitivity analysis indicates that non-proportional growth in EV demand across subdistricts leads to distinct responses in the PEVCS network. Demand growth driven by traffic flow patterns has a greater impact on service performance than residential-based growth. Therefore, decisions regarding PEVCS development should consider not only cost efficiency but also technical characteristics and spatial distribution of demand to ensure equitable and effective charging services.